“The cornerstone is laid”: Italian American Memorial Building in New York City and Immigrants’ Right to the City at the Turn of the Twentieth Century - Bénédicte Deschamps (European Journal of American Studies)
This paper will analyze how, at the end of the nineteenth century, Italian Americans used memorial building to get a greater exposure as an ethnic group, transcend the boundaries of the Little Italies, question the place they had been assigned in American society and history, and redefine their role as political actors of the city.